CT-Guided Celiac Plexus Block and Neurolysis for Chronic Upper Abdominal Pain - Thabet, Ashraf (Digestive Disease Interventions, 2022)
Chronic visceral abdominal pain due to malignant and inflammatory conditions can be challenging to treat, requiring a multidisciplinary approach. Opiates are commonly employed in the palliation of chronic abdominal pain but are complicated by quality of life-limiting side effects such as nausea, vomiting, sedation, and constipation. Celiac plexus block and neurolysis (CPBN) are important tools in the multimodality approach to such pain, with documented improvement in pain scores and, importantly, reduction in opiate demands and improvement in quality of life. It targets the celiac relay station that mediates transmission of visceral nociceptive information from upper abdominal organs; distinguishing from somatic and neuropathic pain is important for clinical success. Key determinants of procedure success include patient selection, understanding relevant anatomy, how that anatomy is distorted by pathology, selection of location for block or neurolysis, as well as distribution and volume administered of injectate during the procedure. CPBN is a safe procedure associated with a low complication rate and may demonstrate better efficacy when used earlier in a patient's disease course.
Keywords: celiac plexus neurolysis; celiac plexus block; cancer pain management